2019
DOI: 10.37358/rc.19.10.7576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liming and Fertilization on the Dehydrogenase and Catalase Activities

Abstract: In this paper we provide new data about the soil enzyme activity as a biological process, which is an indicator for impacts of factorial combinations of lime and fertilizers applications. Five plots divided into fifteen subplots were sampled for determination of the enzymatic indicators of soil quality, based on the actual and potential dehydrogenase and catalase activities. The research revealed that limed soil samples, in comparison with unlimed ones, resulted in significantly higher soil enzymatic activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In support of this hypothesis, our data showed higher chlorophyll contents in MEL plants than those in the control during drought stress conditions. Melatonin is considered a vital plant growth regulator in abiotic stresses especially salt and drought stresses [36][37][38]. The present findings revealed that MEL pretreatment mitigated the adverse effects of drought stress on plant pigments and osmolyte accumulation in maize.…”
Section: Discussionsupporting
confidence: 50%
“…In support of this hypothesis, our data showed higher chlorophyll contents in MEL plants than those in the control during drought stress conditions. Melatonin is considered a vital plant growth regulator in abiotic stresses especially salt and drought stresses [36][37][38]. The present findings revealed that MEL pretreatment mitigated the adverse effects of drought stress on plant pigments and osmolyte accumulation in maize.…”
Section: Discussionsupporting
confidence: 50%
“…Soil enzyme activity is an important indicator of soil biological quality. According to Samuel et al [65], the application of lime to soil increased dehydrogenase and catalase activity significantly, resulting in decomposition of the organic manure and higher nutrient availability. Similarly, the application of chemical fertilizer along with organic fertilizer (green manure and farmyard manure) remarkably increased dehydrogenase, catalase, acid and alkaline phosphatase activities, which resulted in nutri-ent availability and plant biomass production [66].…”
Section: Discussionmentioning
confidence: 99%
“…Using organic matter in plant fertilization increases the microbial/chemical actions and properties of soils [57]. A balanced application of fertilizers concludes to the formation of favorable conditions for the development of microorganisms, growth of plants and for an intense and lasting enzymatic activity [58].…”
Section: Discussionmentioning
confidence: 99%